2018
DOI: 10.1371/journal.pone.0198045
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus genotypes and subgenotypes causing acute hepatitis, Bulgaria, 2013–2015

Abstract: BackgroundIn industrialized areas of the world, including Europe, Hepatitis E Virus (HEV) is considered an emerging pathogen. In fact, autochthonous cases caused by HEV genotype 3 (HEV-3) are increasingly reported. Several studies described the human HEV-3 subtypes and strains circulating in West Europe countries; in contrast, very little is known about the HEV strains responsible for acute hepatitis E in countries of East Europe/Balkans, such as Bulgaria.Methods and findingsAnti-HEV IgM positive serum samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 17 publications
2
42
1
Order By: Relevance
“…However, none of the studies investigated if there is a correlation between HEV in humans and pigs. In Bulgaria, two HEV phylogenetic studies confirmed the presence of HEV Subtypes 3e, 3f, 3c, 3i, and 3hi, and Subtype 1, in human samples [31,52]. Most of these subtypes refer to domestic pigs and wild boar, which reveals the probability of zoonotic transmission of HEV infection to humans.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, none of the studies investigated if there is a correlation between HEV in humans and pigs. In Bulgaria, two HEV phylogenetic studies confirmed the presence of HEV Subtypes 3e, 3f, 3c, 3i, and 3hi, and Subtype 1, in human samples [31,52]. Most of these subtypes refer to domestic pigs and wild boar, which reveals the probability of zoonotic transmission of HEV infection to humans.…”
Section: Discussionmentioning
confidence: 94%
“…Studies on the distribution of HEV in humans across Bulgaria show that the most acute hepatitis E cases in the country are caused by the HEV-3 subtypes 3 e , 3 f and 3 c [ 31 , 32 ]. The first immunological study of pigs in Bulgaria from 2017 reported over 75% seropositivity.…”
Section: Introductionmentioning
confidence: 99%
“…We found 23 papers (PubMed databases – 5; Bulgarian medical databases – 18). Seven articles fulfilled the inclusion and exclusion criteria and were included in the final data analysis (Table 1) [5], [8], [9], [10], [11], [12], [13]. All articles described hospitalised patients with clinical presentation of acute HEV infection.…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic relationships were analysed by constructing a Neighbor‐Joining phylogenetic tree calculated on the Maximum Composite Likelihood distances by MEGA 6.0 as previously described, using a recommended set of standard reference HEV sequences plus additional sequences (Figure ) . Tree reliability was assessed by setting bootstrap replicates to 1000.…”
Section: Methodsmentioning
confidence: 99%
“…Nested PCR and sequencing were performed to obtain an ORF2 472nt sequence from the viremic participant. 33 Briefly, serum-extracted RNA was reverse transcribed with random hexamers, and cDNA was used as nested-PCR template. Purified PCR product underwent automated DNA sequencing (Beckman Coulter, Inc., Fullerton, CA).…”
Section: Hev Sequencing and Sequence Analysismentioning
confidence: 99%